Arterial stiffness in young women with Turner syndrome using cardio-ankle vascular index - Heo, You Jung (Ann Pediatr Endocrinol Metab, 2019)
PURPOSE: Patients with Turner syndrome (TS) have increased risk of morbidities and mortality related to cardiovascular complications. Cardio-ankle vascular index (CAVI) is a novel method of evaluating arterial stiffness independent of changes in blood pressure. We compared arterial stiffness using CAVI between TS patients and healthy control subjects. METHODS: Nineteen young women with TS (mean, 26.8 years; range, 20.0–35.1 years) and 23 healthy women matched for age and body mass index (BMI) were recruited for CAVI measurements at Seoul National University Hospital between 2010 and 2013. Anthropometric parameters, fasting blood testing and measurements of CAVI were compared between the 2 groups. RESULTS: TS patients were significantly shorter (mean: 150.1 cm vs. 160.7 cm, P<0.001) and had lower body weight (mean: 47.0 kg vs. 55.5 kg, P=0.014) than healthy controls, without difference in BMI. CAVI (6.5±0.6 vs. 6.1±0.6, P=0.039) was significantly higher in TS patients compared to healthy controls. Age was positively associated with CAVI (r=0.403, P=0.008) in univariate analysis. After adjusting for age, TS was associated with CAVI (P=0.006). CONCLUSIONS: Young women with TS showed increased arterial stiffness measured by CAVI compared to healthy women after adjusting for age, suggesting inherent vasculopathy in TS patients.